AFASIA MOTORA, PARALISIA FACIAL E HEMIPLEGIA DIREITA APOS ABSCESSO DENTARIO A ESQUERDA - Montovani, Jair Cortez [UNESP]; Nakajima, Victor [UNESP]; Yoshinaga, S. [UNESP]; Yoshinaga, S. L S [UNESP]; Rabello Coelho, C. [UNESP] (My University, 1994)
The authors report a case of a 6 year old child who presented with dental abscess associated with a parietal and frontal cerebrite, right facial paralysis and motor aphasia. The clinical findings, radiological examination including computerized tomography and type of treatment are presented. At beginning, the patient did not respond to antimicrobial therapy and only after drainage of her dental abscess revealed good clinical evolution.
Aphasia motora, facial paralysis and right hemiplegy after left dental abscess
Keywords: aphasia; dental abscess; facial paralysis; abscess; case report; facial nerve paralysis; female; hemiplegia; human; preschool child